A Comparison of Serum Immunoglobulins Lvelels in Aggressive Periodontitis and Chronic Periodontitis - Kumar, Abhima; Sharma, Manik; Kaur, Paravreet; Arodhia, Neeru; Kotwal, Vineet (Asian Journal of Medical Research, 2025)
Background: Classification of 2017 of Periodontal and Peri-Implant disease and Conditions by AAP and EFP, Aggressive periodontitis and Chronic periodontitis was grouped under a single category. Unlike 1999workshop where Periodontitis was reclassified as chronic, aggressive (localised and generalised), necrotising and as a manifestation of systemic disease wherein Aggressive periodontitis and Chronic periodontitis were differentiated on the age of onset, rapid rate of progression, the composition of subgingival microflora, familial aggregation, racial influence and immuneresponse. In this study we aim to show a statistically significant difference in serum antibodies level of both Aggressive periodontitis and Chronic periodontitis, which could be suggestive of difference in implicated primary pathogen and frequency and tissue invasion of microorganism. Subjects and Methods: Two groups consisting of 10 patients each were formed. Group A consisted of patients with aggressive periodontitis and group B consisted of chronic periodontitis, blood samples were taken from both the groups and checked for IGG, IGA, IGM titres. Results: Both the groups were compared for the levels of immunoglobulin levels, group A showed a statistically significant raise in the levels in comparison to group B. While IGG levels were beyond the normal levels in group A. Conclusion: As treatment of aggressive periodontitis should differ from that of chronic periodontitis on the basis of immunological response. Hence clubbing Aggressive periodontitis and Chronic periodontitis in same category in The New Classification from the 2017 can not be justified.